Get out of homelessness. An approach through life stories - Caro Blanco, Fernanda; López-Bermúdez, Alfonso (Cuadernos de Trabajo Social, 2025)
The situations of homelessness addressed in this work are encompassed within the first two conceptual categories proposed by the ETHOS typology: rooflessness and houselessness. Specific processes experienced by individuals who have gone through various forms of social exclusion related to the lack of housing are studied to identify the factors that have facilitated their social integration. The primary objective of this research is to identify the factors that have a positive and significant impact on overcoming homelessness, as narrated by individuals who have experienced these processes. To achieve this objective, a qualitative methodology was employed, using the life history technique. This allowed individuals to identify the impact of their past experiences and articulate their aspirations for the future, highlighting the most significant events in their lives as narrated in the first person. The findings indicate the necessity of incorporating several factors into policies for the prevention and eradication of homelessness. These include the centrality of housing, the need to reform care models in shelters for homeless people, non-stigmatizing support capable of addressing emotional and mental health aspects, the strengthening of social support networks, and the promotion of income guarantee systems and access to employment.
Keywords: homelessness; residential exclusion; life stories; professional support